Problem Peserta Didik di Madrasah Tsanawiyah Pesantren Ilmu Al-Quran (MTs PIQ) Singosari Kabupaten Malang: Student Problems at Madrasah Tsanawiyah Pesantren Ilmu Al-Quran (MTs PIQ) Singosari Malang District - Ludfillah; A. Qomarudin (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2024)
Madrasah is a place for the formation of effective outcomes that have integrity with adequate and well-organized resources. The purpose of this article is to understand the problems of students at the Madrasah Tsanawiyah Pesantren Ilmu Al-Qur’an (MTs PIQ) Singosari District, Malang Regency. This article uses a qualitative approach and a case study type of field research. The results of the research show that: First, the problems of students at MTs PIQ include difficulty understanding the lesson material, not having an effective memorization strategy, lacking motivation to compete and often being late for class. Meanwhile, the solutions implemented are: holding outing class activities, designing learning tools, improving student management in class as well as improving facilities and increasing student discipline. Second, students at MTs PIQ have supporting factors in the form of a 24-hour learning system, financial support and extracurricular activities. Meanwhile, the inhibiting factors are small classrooms and students who are difficult to control. Madrasah merupakan tempat pembentukan luaran yang efektif yang memiliki integritas dengan sumber daya yang memadai dan terorganisasi dengan baik. Tujuan artikel ini memahami problem peserta didik di Madrasah Tsanawiyah Pesantren Ilmu Al-Qur’an (MTs PIQ) Kecamatan Singosari Kabupaten Malang. Artikel ini merupakan menggunakan pendekatan kualitatif dan jenis penelitian lapangan yang bersifat studi kasus. Hasil penelitian menunjukkan bahwa: Pertama, problem peserta didik di MTs PIQ antara lain kesulitan memahami materi pelajaran, belum memiliki stategi hafalan yang efektif, kurang memiliki motivasi berkompetisi dan sering terlambat masuk kelas. Sedangkan solusi yang dilakukan adalah: mengadakan kegiatan outing class, mendesain perangkat pembelajaran, perbaikan pengelolaan peserta didik di kelas serta pembenahan sarana dan peningkatan kedisiplinan peserta didik. Kedua, peserta didik di MTs PIQ memiliki faktor pendukung berupa sistem pembelajaran 24 jam, dukungan dana bantuan dan kegiatan ekstrakurikuler. Sedangkan faktor penghambatnya adalah ruang kelas yang kecil dan peserta didik sulit dikendalikan. Kata Kunci: Problematika, Peserta Didik, Pembelajaran, MTs.